Qur'anic Mizan and Sustainable Islamic Financial Instruments: A Semantic Analysis - Akmal Hidayah; Sujiat Zubaidi; Irfan Maulana Ishaq; Muhammad Hafidh Rafi (JURNAL ECONOMINA, 2026)
This study aims to explore the evolution of meaning and the semantic structure of the term mizan in the Qur’an and to operationalize it as an applied framework for designing modern sustainable Islamic financial instruments. This qualitative library research applies Toshihiko Izutsu’s structural-semantic approach through the analysis of basic meaning, syntagmatic and paradigmatic relational meanings, and the reconstruction of the Qur’anic worldview (weltanschauung). Sacred textual and exegetical data are then triangulated with the Maqasid al-Shari’ah framework to produce holistic financial governance parameters. The findings reveal that the term mizan transformed from a physical-commercial weighing tool in the pre-Islamic era into a paradigm of systemic equilibrium and cosmic-social justice. Practically, the philosophical value of mizan, synthesized with the protection of wealth (hifz al-mal) and life (hifz al-nafs), emphasizes the need to integrate commercial and social finance. The implementation of hybrid instruments, ranging from meso-level Cash Waqf Linked Deposit (CWLD) for sustainable agriculture to macro-level Green Sukuk and Waqf-Linked Sukuk for socio-ecological infrastructure, represents a practical application of mizan. These instruments have the potential to maintain financial stability while mobilizing inclusive capital to achieve ecological sustainability and distributive justice.